The Connection Between Work Motivation and Work Stress with Work Engagement for Bakti Timah Medika Employees - Muchtadin Muchtadin; Zelvy Emmelya Sundary (Jurnal Psikologi Teori dan Terapan, 2023)
This research aims to determine the strength of the relationship between motivation and work stress with work involvement individually or simultaneously. The quantitative approach used in research. The sampling used is the saturated sample method. A total of 270 people filled out the questionnaire with a response rate of 17.21% of the total population. The data analysis method used quantitative descriptive analysis, simple correlation, and multiple correlation. Normality and linearity tests were used before hypothesis testing. The finding in this study is that work motivation is positively and strongly correlated with work engagement. Job stressor has a negative and weak correlation with work engagement. Motivation and work stress are simultaneously positively connected with work engagement. The company is expected to provide motivation, increase the benefits provided and provide freedom in managing work schedules and ways of working so that employees feel more comfortable with their work. Further researchers can use factors that mediate the link between job stress and job engagement to explain the weak relationship found in this study. The next researcher can compare work motivation, job stress and job involvement Penelitian ini bertujuan untuk mengetahui kekuatan hubungan motivasi dan juga stres bekerja dengan work engagement secara masing-masing maupun simultan. Pendekatan kuantitatif dipakai dalam penelitian. Pengambilan sampel yang dipakai ialah metode sampel jenuh. Sebanyak 270 orang yang mengisi kuesioner dengan tingkat respon 17,21% dari total populasi. Metode analisis data memakai analisis deskriptif kuantitatif, korelasi sederhana dan korelasi berganda. Uji normalitas dan linearitas dipakai sebelum pengujian hipotesis. Temuan dalam penelitian ini ialah motivasi kerja berkorelasi positif dan kuat dengan work engagement. Stres kerja berkorelasi negatif dan lemah dengan work engagement. Motivasi dan stres kerja secara berbarengan berkorelasi positif dengan work engagement. Pihak perusahaan diharapkan memberikan pelatihan motivasi, meningkatkan tunjangan yang diberikan serta memberikan kebebasan dalam mengatur jadwal kerja dan cara bekerja agar karyawan lebih merasa terikat dengan pekerjaannya. Peneliti selanjutnya dapat menggunakan faktor yang memediasi hubungan antara stres kerja dengan work engagement guna menjelaskan lemahnya hubungan yang ditemukan dalam penelitian ini. Peneliti selanjutnya bisa juga membandingkan tingkat motivasi kerja, stres kerja dan work engagement pada karyawan yang memiliki posisi pekerjaan yang berbeda.